Institutional Innovation and Co-production as Domestic Waste Handling in Bandung Regency - Neneng Zakiah; Ida Widianingsih; Candradewini Candradewini (Enrichment : Journal of Management, 2021)
This article discusses the handling of domestic waste through institutional innovation and co-production as an alternative in reducing and utilizing organic and inorganic waste. Waste in Bandung Regency is a very serious problem, almost all sub-Regencys experience problems in managing waste, even though the local government has created many waste management programs but the waste problem still continues. Therefore, a new concept is needed with reference to the concept of co-production. Co-production is a concept of joint production that exists between the government and the community to produce innovations in waste management through the Thematic Waste Bank. This writing refers to one variable, namely the role of the government, this article is finding various waste handling innovations designed and managed by the local government with a qualitative analysis approach using interviews with informants from the Bandung Regency Environmental Agency. The result of this study is that the local government has carried out various innovations that prioritize broad public participation and community commitment in dealing with the challenges of solid waste issues in Bandung Regency, but these innovations have not been able to significantly reduce waste generation in Bandung Regency. This Thematic Waste Bank Program does not cover all sub-Regencys in Bandung Regency. The result of this study is that the local government has carried out various innovations that prioritize broad public participation and community commitment in dealing with the challenges of solid waste issues in Bandung Regency, but these innovations have not been able to significantly reduce waste generation in Bandung Regency. This Thematic Waste Bank Program does not cover all sub-Regencys in Bandung Regency. The result of this study is that the local government has carried out various innovations that prioritize broad public participation and community commitment in dealing with the challenges of solid waste issues in Bandung Regency, but these innovations have not been able to significantly reduce waste generation in Bandung Regency. This Thematic Waste Bank Program does not cover all sub-Regencys in Bandung Regency.